The Construction of Social Values of Darun Nadwah in the Film Omar: A Roland Barthes Semiotic Study - Siti Qurotul Aenia Ramadhani; Rohanda Rohanda; Yadi Mardiansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The film Omar presents a historical Islamic narrative containing various symbols that represent social values in Arab society during the early period of Islam. This study aims to examine the construction of social values in the Darun Nadwah scenes of the film Omar by Hany As'ad using Roland Barthes' semiotic approach. This study employs a qualitative descriptive method with data sources consisting of the Darun Nadwah scenes found in the film Omar. Data were collected through the observation method and note-taking technique, focusing on the characters' utterances, facial expressions, costumes, and visual symbols appearing in the selected scenes. Data analysis was conducted through three levels of meaning, namely denotation, connotation, and myth. The results of the study indicate the existence of myths related to titles (laqab), clothing, statues, and characters' expressions that represent the construction of social values in the form of social honor, recognition of social status, reverence for ancestral tradition, and the maintenance of prestige and social influence. The Darun Nadwah scenes represent the social structure of Quraysh society and reveal ideological meanings constructed through both visual and verbal elements in the film. The findings of this study indicate that Roland Barthes' semiotic approach can be used to uncover the representation of social values and ideology hidden behind the signs in audiovisual media.